Factors associated with depression symptoms in high school students in São Paulo, Brazil Fatores associados a sintomas depressivos em estudantes do ensino médio de São Paulo, Brasil - LC Zinn-Souza; R Nagai; LR Teixeira; MRDO Latorre; R Roberts; SP Cooper; FM Fischer (Universidade de São Paulo, 2008)
OBJECTIVE: To assess factors associated with depression symptoms in high school students. METHODS: A cross-sectional study involving high school students was conducted in the city of São Paulo, Brazil, 2001. A total of 724 students aged 14-18 years answered questionnaires on life and health conditions. Another questionnaire was applied to working (44.8%) and unemployed (22.9%) students to collect information on working conditions. Factors associated to depressive disorders were analyzed using multiple logistic regression controlled for occupational status. RESULTS: Overall prevalence rate of depression was 7.5%. Rates according to gender were 39 (10.3%) in females and 15 (4.3%) in males. The multiple logistic regression analysis showed that factors associated with depressive disorders were: poor self-perception of health (OR=5.78), being female (OR = 2.45), and alcohol consumption (OR=2.35). CONCLUSIONS: The study results showed that sociodemographic, lifestyle and health variables were associated with symptoms of depression in this population. These ndings suggest that it is important to have mental health professionals available in high schools for early detection of mental conditions and student counseling. OBJETIVO: Investigar os fatores associados a sintomas depressivos em estudantes do ensino médio. MÉTODOS: Foi realizado estudo transversal com estudantes residentes no Município de São Paulo, Brasil, em 2001. O total de 724 estudantes com idades entre 14 e 18 anos preencheram questionários de condições de vida e saúde. Dentre eles, os estudantes trabalhadores (44,8%) e desempregados (22,9%) também responderam a um outro questionário de condições de trabalho. A regressão logística foi utilizada para determinar os fatores associados para apresentar distúrbios depressivos, utilizando-se a "situação ocupacional" para ajustar o modelo. RESULTADOS: A prevalência dos sintomas depressivos na população estudada foi de 7,5%; as taxas de acordo com o sexo foram de 39 (10,3%) e 15 (4,3%) nos adolescentes dos sexos feminino e masculino, respectivamente. A regressão logística mostrou que os fatores associados aos distúrbios depressivos são: baixo escore na auto-avaliação da saúde (OR=5,78), ser do sexo feminino (OR=2,45) e consumo de bebidas alcoólicas (OR=2,35). CONCLUSÕES: Os resultados mostraram que variáveis sociodemográficas, de estilo de vida e de saúde estavam associadas aos distúrbios depressivos. Esses achados sugerem a importância de que profissionais de saúde mental em escolas de ensino médio efetuem rastreio para reconhecer precocemente problemas mentais e fornecer aconselhamento aos estudantes.